Energy efficiency maturity (EEM) assessment framework for energy-intensive SMEs: Proposal and evaluation. (10th November 2017) - Prashar, Anupama
Abstract: Despite being a key industrial segment in terms production contribution and energy demand, small and medium-sized enterprises (SMEs) have been trailing in the implementation of available energy efficiency (EE) technologies, measures and practices due to both intrinsic and extrinsic barriers. The industrial EE audit programs driven by Government for SMEs had limited success in promoting EE practices due to an "onesize-fit-all" approach instead of a more personalized maturity-based approach towards EE assessment. Some of the energy management maturity models reported in the academic literature integrates the comprehensive requirements of ISO 50001, the international energy management standard, with the established maturity assessment instruments. However, these models are of little use to the SMEs due to the lack of resources and professional knowledge with the SMEs to meet ISO 50001 requirements. This study conceptualized and validated an energy efficiency maturity (EEM) framework for energy-intensive SMEs to facilitate a pre-assessment of EE maturity profile and draw out a personalized improvement plan. The framework consisted of three elements: EE characteristics & dimensions (derived from literature); EE maturity levels; and the Implementation method (adapted from Zero Defect Zero effect or ZED scheme designed for Indian SMEs). For validation of the EEM framework, a case of an Indian small-scale steel re-rolling mill (SRRM) was selected. The mill was rated at "Level 2 - Beginner" during the pre-assessment using the EEM instrument reached to "Level 4 - Achiever" after completion of first set of need-based EE improvement projects. These projects were attempted to build specific EE dimensions such as Energy Management roles; EE opportunity reporting; Product/Process innovation for optimization of energy use, which the mill lacked during the pre-assessment. Highlights: Energy Efficiency Maturity (EEM) framework to support the Energy Efficiency (EE) practices in the energy-intensive SMEs. The framework defines 7 EE dimensions and 5 levels of maturity for the assessment. It allows assessment of current maturity of the SME and establishment of an effective growth plan. The steel re-rolling mill case illustrates the growth in maturity level through systematic implementation of EE practices.